Integrative Analysis of Metabolome and Transcriptome Reveals Molecular Insight into Metabolomic Variations during Hawthorn Fruit Development - Yan Wang; Ruixin Hao; Rongkun Guo; Huilan Nong; Yu Qin; Ningguang Dong (Metabolites, 2023)
Hawthorn (Crataegus pinnatifida var. major), a cultivated fruit tree, is native and unique to China. Its fruits have high nutritional, health, and medicinal values. However, the development and ripening process of hawthorns is accompanied by dramatic changes in flavor, aroma, and bioactive phytochemicals, which are the fundamental factors that contribute to the potential health benefits and establishment of fruit quality. Therefore, an exploration of the dynamic changes in metabolites and their regulatory networks during the development of hawthorn fruits can elucidate the formation mechanisms of active substances in hawthorn fruits. In this study, we used a broad targeted metabolomics approach to identify and analyze the dynamics of metabolites in hawthorn fruits at five developmental stages. The results revealed 998 primary and secondary metabolites that were classified into 15 categories. The accumulation levels of most sugars increased during fruit development and then accelerated at the fruit ripening stage. The accumulation levels of a few organic acids (e.g., citric acid, isocitric acid, and quinic acid) continuously increased. Many organic acids exhibited significant decreasing trends. Among the 561 secondary metabolites detected, 189 were phenolic acids and 199 were flavonoids. The levels of many flavonoids were significantly reduced at later stages of fruit development; in contrast, the levels of two anthocyanins significantly increased during fruit ripening. Correlation analysis revealed that there is a certain correlation within and between primary as well as secondary metabolites during fruit development. Furthermore, the integration of metabolomic and transcriptomic data in this study revealed that changes in the expression of some differentially expressed genes (DEGs) were associated with the accumulation of metabolites such as sugars, organic acids, and flavonoids, e.g., the upregulated expression levels of CS (citrate synthase) genes were consistent with the continued accumulation of citric acid. Overall, this study demonstrates the metabolic changes that occur during the development of hawthorn fruit, explores the molecular mechanisms that underlie metabolite changes during fruit development, and lays a strong theoretical foundation for the improvement of hawthorn fruit quality and the development of functional components.